Selected Properties of Sustainable Hemp Shives Based Magnesium Composite Compacted in Two Directions and Its Life Cycle Assessment - Przemysław Brzyski; Līga Puzule; Māris Šinka; Jakub Wankiewicz; Diāna Bajāre (Journal of Natural Fibers)
The study aims to assess the impact of variable binder content and the direction of compaction on the properties of the hemp-magnesium composites. These two factors may influence the scope of application of the developed composites (e.g. as a lightweight insulating filling of a frame wall, or a heavier material for load-bearing applications or in prefabrication). Capillary rise, thermal conductivity, compressive and flexural strength in two directions, as well as the absorbability were tested. An analysis of the environmental impact of the composites was also prepared. When a magnesium binder is used, it is possible to produce lightweight composites with low thermal conductivity (0.07 W/(m∙K)), but also heavier ones with high compressive (1.73 MPa) and flexural (0.98 MPa) strength. It is possible to improve selected parameters after changing the direction of compaction. The thermal conductivity of composites compacted in a direction parallel to the heat flow was lower by 17–25% compared to a perpendicular direction. The positive effects of changing the direction of compaction can be used in prefabrication by adjusting the compaction process. The impact on climate change varies significantly due to the proportion of these materials from 55.07 kg CO2 eq. to 358.64 kg CO2 eq.